Hepatic Thrombopoietin mRNA Is Increased in Acute Inflammation - Wolber, Eva-Maria; Fandrey, Joachim; Frackowski, Urszula; Jelkmann, Wolfgang (Thrombosis and Haemostasis, 2001)
The plasma concentration of thrombopoietin (TPO) in general is inversely related to the mass of platelets and megakaryocytes. However, reactive thrombocytosis of inflammatory disease is accompanied by elevated TPO levels. To investigate whether the rate of TPO mRNA expression is altered during acute inflammation, rats were injected with bacterial lipopolysaccharide (LPS). After 6 h, total RNA from liver and kidney was reverse transcribed and analyzed by competitive PCR for TPO and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). LPS-treated rats showed a significant increase in hepatic TPO mRNA concentration. The ratio of TPO to GAPDH mRNA was 3.5 ± 0.6% in the livers of control rats and 8.3 ± 2.0% in the livers of LPS-treated rats (mean ± SD). Thus, reactive thrombocytosis of inflammatory disease might result from an increase in hepatic TPO production. Since platelets are involved in the immune reaction, reactive thrombocytosis may be a mechanism of host defense.
Keywords: Thrombopoietin; inflammation; reactive thrombocytosis; acute phase reaction; LPS